Thermophysical, Rheological and Morphological Properties of Polyoxymethylene Polymer Composite for Additive Technologies; Russian Physics Journal; Vol. 61, iss. 6 - Lebedev S. M. Sergey Mikhailovich; Gefle O. S. Olga Semenovna; Amitov E. T. Ernar Tanirbergenuly; Berchuk D. Yu. Denis Yurievich; Zhuravlev D. V. Denis Vladimirovich (2018, 2018)
Title screen